Religious Moderation: The Dialectic between the Normativity of Revelation and the Historicity of Social Practice - Andrianto; Akbar Waliyuddin Pakpahan; Rika Amalia (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2026)
Moderate religiosity has become a crucial issue in Islamic education amid increasing social pluralism and the complexity of religious expressions in public spaces, particularly within public universities. This study examines the implementation of religious moderation in Islamic Education at Universitas Negeri Yogyakarta (UNY) by focusing on the dialectical relationship between the normativity of revelation and the historicity of social practices. The research addresses a scientific gap concerning how Islamic normative values are contextually negotiated within academic environments that are socio-culturally diverse and institutionally secular. Employing a qualitative reflective-interpretative approach, data were collected through document analysis of curricula and instructional designs, supported by in-depth interviews and limited observations of learning practices. Data were analyzed thematically using a hermeneutic and sociology of knowledge framework. The findings indicate that religious moderation in Islamic Education at UNY functions as an epistemological mediation that bridges transcendental religious values and socially constructed realities. Rather than diluting Islamic norms, moderation facilitates contextualization that fosters reflective, dialogical, and ethically responsible religious understanding among students. This approach contributes to the development of inclusive academic ethos and strengthens students’ capacity to engage constructively with religious diversity. The study implies that integrating religious moderation into Islamic Education enhances the relevance of religious teachings in plural academic settings and supports the formation of socially responsible and intellectually autonomous Muslim graduates.